Analisis Rasio 3 - Bank Komersial dengan Uji - Rls: Implikasi dan Bukti Kinerja Keuangan Bank Indonesia dan Malaysia - Lucky, Muhammad; Zawawi, Abdullah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Abstracts This research aims to analyze the interaction between commercial banks in Indonesia and commercial banks in Malaysia on bank financial performance reports seen from the ratio aspect of bank financial reports. The method used in this research is a quantitative descriptive method by knowing the existence of the Dependent variable value on the variable (Independent) or more without making relationships and comparisons with other variables. In terms of bank value using the 3 - RLS implementation route, namely, the bank's Profitability Ratio is calculated by looking for Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), and Operating Expenses / Operating Income (BOPO). The Liquidity Ratio is calculated by finding the Quick Ratio (QR), Loan to Deposit Ratio (LDR), and Loan to Assets Ratio (LAR). The Solvency Ratio is calculated by looking for the Capital Adequacy Ratio (CAR) and Debt to Equity Ratio (DER). The results of this research evaluate and see the feasibility of 3 commercial banks in Indonesia and Malaysia against the Central Bank using the Triple - RLS method concept. As for commercial banks, there is policy integration with central bank criteria. Therefore, there needs to be discipline and commitment in improving financial performance in financial reports between Indonesian and Malaysian commercial banks.